Continuously prepared highly conductive and stretchable SWNT/MWNT synergistically composited electrospun thermoplastic polyurethane yarns for wearable sensing. Issue 9 (14th December 2017) - Li, Yahong; Zhou, Bing; Zheng, Guoqiang; Liu, Xianhu; Li, Tingxi; Yan, Chao; Cheng, Chuanbing; Dai, Kun; Liu, Chuntai; Shen, Changyu; Guo, Zhanhu
Abstract : Highly conductive and stretchable electrospun thermoplastic polyurethane yarns with multi-walled and single-walled CNTs were prepared. Abstract : Highly conductive and stretchable yarns have attracted increasing attention due to their potential applications in wearable electronics. The integration of conductive yarns with large stretching capability renders the composite yarns with new intriguing functions, such as monitoring human body motion and health. However, simultaneously endowing the yarns with high conductivity and stretchability using an easily scalable approach is still a challenge. Here, highly conductive and stretchable yarns based on electrospun thermoplastic polyurethane (TPU) fiber yarns successively decorated with multi-walled carbon nanotubes (MWNTs) and single-walled carbon nanotubes (SWNTs) were prepared by a combined electrospinning, ultrasonication adsorbing, and bobbin winder technique. The improved thermal stability of the SWNT/MWNT/TPU yarn (SMTY) indicated strong interfacial interactions between the CNTs and electrospun TPU fibers. The synergism between the successively decorated SWNTs and MWNTs significantly enhanced the conductivity of the TPU yarns (up to 13 S cm −1 ). The as-fabricated yarns can be easily integrated into strain sensors and exhibit high stretchability with large workable strain range (100%) and good cyclic stability (2000 cycles). Moreover, such yarn can be attached to the human body or knitted into textiles to monitor joint motion, showing promising potential for wearable electronics, such as wearable strain sensors.